Epidicus by Plautus : An Annotated Latin Text, with a Prose Translation - Tracy, Catherine (Open Book Publishers, 2021)
Epidicus, a light-hearted comedy by Plautus about the machinations of a trickster slave and the inadequacies of his bumbling masters, appears here in both its original Latin and a sparkling new translation by Catherine Tracy. Epidicus, the cunning slave, is charged with finding his master$1 (Bs illegitimate daughter and the secret girlfriend of his master$1 (Bs son, but a comedy of mistaken identities and competing interests ensues. Amid the mayhem, Epidicus aims to win his freedom whilst risking some of the grislier punishments the Romans inflicted on their unfortunate slaves. This parallel edition in both Latin and English, with its accessible introduction and comprehensive notes, guides the reader through this popular Roman play. Tracy explores Epidicus$1 (Bs roots in Greek drama, its rich social resonances for a Roman audience and its life in performance. She transforms Plautus' colloquial Latin poetry into lively modern English prose, illuminating the play$1 (Bs many comedic references to the world of the Roman republic. This fine introduction to an enduring play will be of great use and enjoyment for undergraduate students of Latin drama and the general reader alike.s
English
Keywords: Classical texts; Classical history / classical civilisation; Designed / suitable for A & AS Level; Translation & interpretation; Classics; comedy; Epidicus; Latin; Plautus; Roman play; translation